Targeting immune cell migration as therapy for inflammatory disease: a review - Song, Bingfeng; Guo, Wenbo; He, Ying; Yao, Xingli; Sun, Jintang; Wang, Shijun (Frontiers in Immunology, 2025)
Immune cell migration plays a pivotal role in coordinating inflammatory responses and maintaining immune surveillance. Here, we provide a comprehensive overview of the migratory behaviors of key immune cell subsets, including Th1, Th2, regulatory T cells, macrophages, dendritic cells, and neutrophils and the molecular mechanisms that guide their trafficking from lymphoid organs to inflamed tissues. We highlight the stepwise migration cascade: priming in secondary lymphoid organs, trafficking through blood vessels, adhesion to endothelium, and extravasation into tissues. Each step is critically regulated by chemokines, selectins, integrins, and proteases. We also examine current pharmacological strategies that target immune cell migration in inflammatory diseases, such as integrin blockers and chemokine receptor antagonists, emphasizing both therapeutic potential and clinical limitations. In addition, we discuss emerging technologies including intravital imaging, CRISPR-based screening, and computational modeling that provide novel insights into immune cell dynamics and may guide the development of next generation migration-targeted therapies. Overall, this review integrates fundamental immunological principles with translational medicine by identifying key challenges, unresolved controversies, and future directions in the therapeutic modulation of immune cell migration.